A recessive C-terminal Jervell and Lange-Nielsen mutation of the KCNQ1 channel impairs subunit assembly - Schmitt, Nicole (Oxford University Press, 2000)
The LQT1 locus (KCNQ1) has been correlated with the most common form of inherited long QT (LQT) syndrome. LQT patients suffer from syncopal episodes and high risk of sudden death. The KCNQ1 gene encodes K(v)LQT1 α–subunits, which together with auxiliary IsK (KCNE1, minK) subunits form IK(s) K(+) channels. Mutant K(v)LQT1 subunits may be associated either with an autosomal dominant form of inherited LQT, Romano–Ward syndrome, or an autosomal recessive form, Jervell and Lange-Nielsen syndrome (JLNS). We have identified a small domain between residues 589 and 620 in the K(v)LQT1 C–terminus, which may function as an assembly domain for K(v)LQT1 subunits. K(v)LQT1 C–termini do not assemble and K(v)LQT1 subunits do not express functional K(+) channels without this domain. We showed that a JLN deletion–insertion mutation at K(v)LQT1 residue 544 eliminates important parts of the C–terminal assembly domain. Therefore, JLN mutants may be defective in K(v)LQT1 subunit assembly. The results provide a molecular basis for the clinical observation that heterozygous JLN carriers show slight cardiac dysfunctions and that the severe JLNS phenotype is characterized by the absence of K(v)LQT1 channel.